A skull from Puerto Cabello as an example of anusual bone thickness in Homo sapiens recens - Rajwerówna-Rudnicka, Hanna (Anthropological Review, 1979)
A modern skull from Puerto Cabello, Venezuela, deposited in an osteometric collection of the Institute of Anthropology of Polish Academy of Sciences constitutes an example of unusual bone thickness unreported for any other modern human individual. A thorough medical examination of this skull failed to find any pathological processes that could possibly account for abnonmal bone thickness. The paper presents a number of measurements of thickness of the skull vault together with a photographic documentation.